An attack-resilient distributed energy management strategy for integrated energy systems - Li, Tong; Sun, Feng; Chen, Jian; Wang, Lei; Yang, Zhibin; Liu, Ruitong; Qi, Jun (Frontiers in Energy Research, 2024)
The increasing integration of various energy sources and the adoption of smart grid technologies have revolutionized the way we generate, distribute, and consume energy. While these advancements offer numerous benefits, they also introduce vulnerabilities to cyber–physical attacks. To this aim, this paper investigates a resilient energy management strategy for integrated energy systems. By adopting a switched control approach and incorporating a local estimation mechanism, we have developed a resilient distributed energy management strategy to tackle the energy management problem (EMP) in integrated energy systems (IESs). This methodology demonstrates strong robustness and resilience, successfully detecting data integrity attacks and denial-of-service (DoS) attacks. Finally, we provide a case study to demonstrate the effectiveness of our proposed strategy in a real-world scenario.